Relation of Profit Rate to Industry Concentration: American Manufacturing, 1936-1940 - Bain, Joe S. (Quarterly Journal of Economics, 1951)
I. The concentration-profits hypothesis, 294. — II. Industry definition, measure of concentration, and selection of sample, 297. — III. Character and limitations of profit data, 305. — IV. Calculation of accounting profit rates, 310. — V. Association of industry profit rates and concentration, 311. — VI. Association of firm profit rates and industry concentration, 317. — VII. Association of profit rates with other determinants, 321. — VIII. Summary, 323.